Phase Changes of Monosulfoaluminate in NaCl Aqueous Solution - Seyoon Yoon (Materials, 2016)
Monosulfoaluminate (Ca4Al2(SO4)(OH)12∙6H2O) plays an important role in anion binding in Portland cement by exchanging its original interlayer ions (SO42− and OH−) with chloride ions. In this study, scanning transmission X-ray microscope (STXM), X-ray absorption near edge structure (XANES) spectroscopy, and X-ray diffraction (XRD) were used to investigate the phase change of monosulfoaluminate due to its interaction with chloride ions. Pure monosulfoaluminate was synthesized and its powder samples were suspended in 0, 0.1, 1, 3, and 5 M NaCl solutions for seven days. At low chloride concentrations, a partial dissolution of monosulfoaluminate formed ettringite, while, with increasing chloride content, the dissolution process was suppressed. As the NaCl concentration increased, the dominant mechanism of the phase change became ion exchange, resulting in direct phase transformation from monosulfoaluminate to Kuzel’s salt or Friedel’s salt. The phase assemblages of the NaCl-reacted samples were explored using thermodynamic calculations and least-square linear combination (LC) fitting of measured XANES spectra. A comprehensive description of the phase change and its dominant mechanism are discussed.